Investigation of structure and properties of hightemperature superconductors LаFeAsO(1 – х)Fх by means of the Mössbauer effect - Lomonosov, Vladimir A.; Kholmetskii, Alexander L.; Makhnach, Leonid V.; Alduchenkov, Aleksey V.; Gerashchenko, Oleg V.; Okunev, Igor S.; Mashlan, Miroslav; Yarman, Tolga (Journal of the Belarusian State University. Chemistry, 2018)
The results of investigation of iron-containing superconductors LаFeAsO(1 – х)Fх (х = 0,11…0,15) are presented, based on joint analysis of Mössbauer spectroscopy, XRD, magnetic and electrophysical methods. A full suppression of magnetic order in these samples with the appearance of the Kondo effect is shown at x = 0.15 and T < 40 K, as well as the transformation of Kondo effect into high-temperature superconductivity at х = 0.11…0.14 and T < 25 K. The revealed effects allow assuming a significant contribution of interaction between magnetic moments of conducting electrons and impurities in the Cooper pair formation for iron-containing superconductors.